2021
DOI: 10.7150/thno.55006
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptome dissection of the toxic impact of Di (2-ethylhexyl) phthalate on primordial follicle assembly

Abstract: Rationale: Accumulated evidence indicates that environmental plasticizers are a threat to human and animal fertility. Di (2-ethylhexyl) phthalate (DEHP), a plasticizer to which humans are exposed daily, can trigger reproductive toxicity by acting as an endocrine-disrupting chemical. In mammals, the female primordial follicle pool forms the lifetime available ovarian reserve, which does not undergo regeneration once it is established during the fetal and neonatal period. It is therefore critical to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 79 publications
1
26
0
Order By: Relevance
“…At this point, there are still plenty of oocytes remaining in the ovarian cysts. Consistent with previous studies Liu et al, 2019;Liu W. X. et al, 2021;Tian et al, 2021;Wang et al, 2021), the effect of the drug on germ cell cyst breakdown and PF formation could be measured by counting the proportion of oocytes in cysts and follicles. In addition, newborn mice were fed normally after 4 days of intraperitoneal injection.…”
Section: Animals and Reagentssupporting
confidence: 60%
See 1 more Smart Citation
“…At this point, there are still plenty of oocytes remaining in the ovarian cysts. Consistent with previous studies Liu et al, 2019;Liu W. X. et al, 2021;Tian et al, 2021;Wang et al, 2021), the effect of the drug on germ cell cyst breakdown and PF formation could be measured by counting the proportion of oocytes in cysts and follicles. In addition, newborn mice were fed normally after 4 days of intraperitoneal injection.…”
Section: Animals and Reagentssupporting
confidence: 60%
“…In fact, many previous studies have confirmed that the obstruction of germ cell cyst breakdown and PF assembly are related to insufficient oocyte-specific gene expression (Wang Y. Y. et al, 2017;Wang et al, 2021;Wang J. J. et al, 2018;Liu J. C. et al, 2021). Interestingly, LH or FSH could reduce the effects of nicotine on specific gene expressions in oocytes, such as factor in the LIM homeobox 8 (Lhx8), growth differentiation factor-9 (Gdf9), spermatogenesis and oogenesis helix-loop-helix 2 (Sohlh2), and newborn ovary homeobox (Nobox; Figure 2A).…”
Section: Lh and Fsh Rescues The Impaired Oocyte-specific Gene Expressionmentioning
confidence: 99%
“…One group utilized scRNA-seq technology, although not directly related to cancer research, to investigate the transcriptomic changes induced by a known xenoestrogen, di (2-Ethylhexyl) phthalate (DEHP), exposure. They revealed the reproductive toxicity of DEHP in murine germ cells and pre-granulosa cells at a single-cell level [138]. Although scRNA-seq has some limitations, such as technical noise from the cell preparation process, loss of spatial information, higher costs than other models, and requirement for freshly prepared samples [139][140][141], it serves as an excellent option for studying the complicated activity of xenoestrogens/phytoestrogens in heterogeneous cell populations of target tissues.…”
Section: Single-cell Rna-sequencing (Scrna-seq)mentioning
confidence: 99%
“…Menopause is a critical WOS because of its hypersensitivity to endocrine-disrupting chemicals due to the decline of endogenous estrogen [208]. Studies from our group have discovered that PBDEs, the flame retardants in household products, enhance E2-mediated regrowth of mammary glands, augment E2-facilitated gene expression, and modulate immune regulation, thus increasing the risk of developing breast cancer [136][137][138][139]. Importantly, like the WOS in female breast cancer, there appears to be a heightened sensitivity of the prostate to these exogenous estrogens during the critical developmental windows, such as in utero, the neonatal period and puberty.…”
Section: Effects Of Xenoestrogens/phytoestrogens Determines On Critical Timing Of Exposurementioning
confidence: 99%
“…Although a large number of MPs and DEHP are removed from the nal e uent of the sewage treatment plant, MPs (2.419×10 MP/d) and DEHP still enter the water environment every day, posing a threat to the health of sh and local residents (Takdastan, Niari et al 2021). Human and animal exposure to DEHP through ingestion, inhalation and skin absorption can cause liver and kidney damage (Camacho, Latendresse et al 2020), male and female reproductive disorders and developmental toxicity (Wang, Tian et al 2021). In addition, it is reported that DEHP induces the formation and apoptosis of carp neutrophil extracellular traps (Nets) by promoting ROS burst and autophagy (Yirong, Shengchen et al 2020).…”
Section: Introductionmentioning
confidence: 99%